Effects of folic acid supplementation on serum homocysteine levels, lipid profiles, and vascular parameters in post-menopausal Korean women with type 2 diabetes mellitus - Vijayakumar, Aswathy (Nutr Res Pract, 2017)
BACKGROUND/OBJECTIVES: Complications of diabetes, such as cardiovascular disease, are associated with increased mortality among type 2 diabetes mellitus patients. Homocysteine has been recently identified as a predictor of cardiovascular disease-related complications in diabetes. We investigated whether or not supplementation with folic acid tablets can lower homocysteine levels and improve parameters related with vascular complications. SUBJECTS/METHODS: We conducted a non-randomized 8-week trial involving postmenopausal diabetic women (n = 25) supplemented with 800 µg of folic acid (400 µg twice a day) daily. Subjects' serum levels of folate, homocysteine, and vitamin B(12) were measured, along with vascular function and brachial-ankle pulse wave velocity. RESULTS: Folic acid supplementation significantly increased serum folate levels (P < 0.0001), reduced homocysteine levels (P < 0.0001), and increased vitamin B(12) levels (P = 0.0063). There were significant decreases in low-density lipoprotein cholesterol levels as well as the ratios of low-density lipoprotein cholesterol to high-density lipoprotein cholesterol and total cholesterol to high-density lipoprotein cholesterol. Brachial-ankle pulse wave velocities were not altered by supplementation. Changes in serum vitamin B(12) after folic acid supplementation were negatively correlated with changes in brachial-ankle pulse wave velocity. CONCLUSIONS: In this study on postmenopausal Korean women with type 2 diabetes mellitus, folic acid supplementation reduced serum homocysteine levels, increased serum folate and vitamin B(12) levels, and lowered lipid parameters.